Assessment of Cognition and Personality as Potential Endophenotypes in the Western Australian Family Study of Schizophrenia. - McCarthy, N.; Badcock, J.; Clark, M.; Knowles, E.; Cadby, G.; Melton, Phillip; Morgan, V.; Blangero, J.; Moses, E.; Glahn, D.; Jablensky, A. (Oxford Journals in Association with The Maryland Psychiatric Research Centre, 2017)
Phenotypic heterogeneity is a major barrier to understanding the genetic architecture underlying schizophrenia. Incorporating endophenotypes is one way to reduce heterogeneity and facilitate more powerful genetic analysis. Candidate endophenotypes require systematic assessment against endophenotype criteria, and a ranking of their potential utility for genetic analysis. In this study we assess 20 cognitive and personality measures in a sample of 127 families with at least 2 cases of schizophrenia per family (n = 535) plus a set of 30 control families (n = 121) against 4 endophenotype criteria: (a) be associated with the illness but not be a part of its diagnosis, (b) be heritable, (c) co-segregate with the illness in families, and (d) be found in unaffected relatives at a higher rate than in the general population. The endophenotype ranking score (endophenotype ranking variable [ERV]) was used to rank candidate endophenotypes based on their heritability and genetic correlation with schizophrenia. Finally, we used factor analysis to explore latent factors underlying the cognitive and personality measures. Evidence for personality measures as endophenotypes was at least equivalent to that of the cognitive measures. Factor analysis indicated that personality and cognitive traits contribute to independent latent dimensions. The results suggest for this first time that a number of cognitive and personality measures are independent and informative endophenotypes. Use of these endophenotypes in genetic studies will likely improve power and facilitate novel aetiological insights.